Composite electrolyte membrane for inhibiting growth of lithium dendrites of solid-state battery, preparation method of composite electrolyte membrane and battery
By using a two-layer electrolyte membrane structure and doped halide in solid-state batteries, the problems of lithium dendrites and interface impedance are solved, the density of the electrolyte membrane and lithium ion conductivity are improved, and the cycle stability of the battery is extended .
Patent Information
- Application Number
- CN202411256458.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-24
AI Technical Summary
There are problems with lithium dendrites growth and interface impedance in solid-state batteries, which limits the application and development of sulfide electrolytes in lithium batteries.
Adopt two-layer electrolyte membrane structure, the first layer of electrolyte membrane particle size is less than 2um, the second layer of electrolyte membrane particle size is 2-10um, and halides, such as LiI, are doped in the first layer of electrolyte membrane, to form a passivation layer to isolate it. The side reaction between the electrolyte and the negative electrode inhibits the growth of lithium dendrites.
Effectively reduce interface impedance, increase contact area, improve the density and mechanical stability of the electrolyte membrane, significantly improve the conductivity of lithium ion, and extend the stable cycle life of lithium metal negative electrodes.
Smart Images

Figure CN119181845A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery, a preparation method thereof, and a battery, and belongs to the technical field of solid-state electrolytes. Background Art
[0002] An all-solid-state lithium battery is a lithium battery in which the electrode and electrolyte materials used within the operating temperature range are solid and do not contain any liquid components. Compared with traditional lithium-ion batteries that use organic liquids as electrolytes, it has the advantages of higher safety and higher energy density, and is a battery material with great development prospects.
[0003] In solid-state batteries, common solid electrolytes can be divided into polymers, oxides, sulfides, complex hydrides and halides. Among them, sulfide-based solid electrolytes have high ion conductivity. At the same time, due to the high capacity, low economic cost and large-scale processability of sulfide-based solid-state lithium batteries, they are very suitable for the development of electric vehicle power batteries and are expected to become one of the important power sources in the future.
[0004] However, in solid-state batteries, there is a certain interfacial impedance between the electrolyte and the negative electrode, as well as problems such as interfacial side reactions and lithium dendrite growth. These problems hinder the further development of solid-state electrolytes in the future and also limit the application of sulfide electrolytes in lithium batteries. Summary of the invention
[0005] In order to solve the above problems, a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries and a preparation method and a battery are provided. The present application sets a two-layer electrolyte membrane structure, specifically defines the composition of the first electrolyte membrane and the second electrolyte membrane, and the particle size of the electrolyte of the two electrolyte membranes; by limiting the electrolyte particle size of the two electrolyte membranes, the electrolyte membrane with a small particle size electrolyte is set close to the negative electrode to increase the contact area and reduce the interface impedance, and the electrolyte membrane with a large particle size electrolyte is set to ensure the overall density of the electrolyte membrane.
[0006] According to one aspect of the present application, a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries is provided, comprising a two-layer electrolyte membrane structure; the first layer of the electrolyte membrane comprises a sulfide electrolyte and a binder; the second layer of the electrolyte membrane comprises a sulfide electrolyte and a binder; the particle size of the electrolyte in the first layer of the electrolyte membrane is less than 2um, and the particle size of the electrolyte in the second layer of the electrolyte membrane is 2-10um.
[0007] Optionally, the first electrolyte membrane further includes a halide, and the halide is one or more of LiI, LiF, LiCl or LiBr.
[0008] Specifically, by doping halides in the first layer of electrolyte, the halides are evenly distributed between the negative electrode and the electrolyte to form a passivation layer, which isolates the side reactions between the electrolyte and the negative electrode, inhibits lithium dendrites, and prevents damage to the interface during lithium deposition.
[0009] Specifically, as electronic insulators, halides have low lithium ion diffusion energy barriers and high surface energy, which can ensure uniform deposition of lithium metal and effectively inhibit the nucleation and growth of lithium dendrites; in addition, the halogenated interface also has excellent mechanical stability, and the extremely high Young's modulus and shear modulus can effectively prevent the damage of the interface during lithium deposition, and provide support for the lithium metal negative electrode and long-term stable cycle; for the lithium ion conductivity of the halogenated interface, although the lithium ion conductivity of the halide itself is extremely low, the introduction of halides in the interface will greatly increase the content of grain boundaries and phase interfaces in the interface layer, which will significantly improve the lithium ion conductivity of the halogenated interface that relies on the grain boundaries and phase interfaces to transfer lithium ions.
[0010] Preferably, the halide is LiI.
[0011] Specifically, I 3- It can also react with dead lithium to achieve uniform deposition of lithium, providing support for the stable long-term cycle of the battery.
[0012] Optionally, the electrolyte is an oxide electrolyte or a sulfide electrolyte; wherein the oxide electrolyte is LLZO or LLTO; wherein the sulfide electrolyte is Li6PS5Cl, Li 10 SnPS 12 , Li6PS5Br and Li 10 GeP2S 12 One or more of the .
[0013] Optionally, the binder includes one or more of NRR, SBR, SEBS, SEPS, PTFE, PVDF, PVDF-HFP, PAA and PAA-Li.
[0014] Preferably, the binder is nitrile rubber.
[0015] According to another aspect of the present application, a method for preparing the composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery is also provided, comprising the following steps:
[0016] (1) mixing a sulfide electrolyte, a solvent, and a binder to prepare a slurry to obtain a first electrolyte slurry, coating the first electrolyte slurry on the negative electrode sheet, and allowing the slurry to stand until the surface solvent evaporates to obtain a first electrolyte membrane;
[0017] (2) A sulfide electrolyte, a solvent, and a binder are mixed to prepare a slurry to obtain a second electrolyte slurry; the second electrolyte slurry is coated on the first electrolyte membrane, and the surface is dried in air and then vacuum dried to obtain a composite electrolyte membrane.
[0018] Optionally, the solvent includes one or more of isobutyl isobutyrate, butyl butyrate, dichloromethane, benzyl methane, xylene and n-decane; the mixing and slurrying in step (1) further includes adding a halide;
[0019] In step (2), the vacuum drying temperature is 80°C-100°C; the vacuum drying time is 10h-14h;
[0020] In step (1), the coating thickness of the first electrolyte slurry is 50-200 um; in step (2), the coating thickness of the second electrolyte slurry is 100-400 um; and the sum of the coating thickness of the first electrolyte slurry and the coating thickness of the second electrolyte slurry is greater than 300 um.
[0021] Optionally, the solid content of the first electrolyte slurry is 25%-35%, the doping ratio of the halide is 1%-10%, and the content of the binder is 3%-5%; the solid content of the second electrolyte slurry is 30%-40%, and the content of the binder is 3%-5%.
[0022] According to another aspect of the present application, the present application also provides a battery, comprising a positive electrode, a negative electrode and the above-mentioned composite electrolyte membrane or the composite electrolyte membrane prepared by the above-mentioned preparation method located between the positive electrode and the negative electrode.
[0023] According to another aspect of the present application, a method for preparing the above-mentioned battery is also provided, comprising the following steps:
[0024] (1) Preparing a silver-carbon pole piece: mixing nano silver powder, C65 and a binder by ball milling to obtain a silver-carbon slurry; coating the silver-carbon slurry on a substrate, and drying to obtain a silver-carbon pole piece;
[0025] (2) mixing a sulfide electrolyte, a solvent, a binder and a halide to prepare a slurry to obtain a first electrolyte slurry, coating the first electrolyte slurry on the silver-carbon electrode, and allowing the slurry to stand until the surface solvent evaporates, thereby forming a first electrolyte membrane on the silver-carbon electrode;
[0026] (3) mixing a sulfide electrolyte, a solvent, and a binder to prepare a slurry to obtain a second electrolyte slurry; coating the second electrolyte slurry on the first electrolyte membrane, drying the surface in a vacuum, and obtaining an AgC / electrolyte composite electrode;
[0027] (4) Laminating the AgC / electrolyte composite electrode sheet to the positive electrode sheet and performing static pressure treatment;
[0028] (5) Performing tab welding and vacuum packaging to obtain a battery.
[0029] Optionally, in step (1), the substrate includes copper foil, aluminum foil or stainless steel foil; the binder includes one or more of NRR, SBR, SEBS, SEPS, PTFE, PVDF, PVDF-HFP, PAA and PAA-Li; the mass ratio of the nano silver powder, C65 and the binder is 1:3:0.1-0.25; and the concentration of the binder is 1% to 10%.
[0030] Optionally, in step (1), the silver-carbon slurry coating thickness is 30-300um, the drying temperature is 30-80°C, and the drying time is 5-20min; in step (4), the static pressure treatment pressure is 300-600MPa, and the temperature is 25-120°C.
[0031] The beneficial effects of this application include but are not limited to:
[0032] 1. According to a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries in the present application, the present application sets a two-layer electrolyte membrane structure, and specifically defines the composition of the first electrolyte membrane and the second electrolyte membrane, and specifically defines the particle size of the electrolyte of the two electrolyte membranes; by limiting the electrolyte particle size of the two electrolyte membranes, the electrolyte membrane with a small particle size electrolyte is close to the negative electrode, thereby increasing the contact area and reducing the interface impedance, and the electrolyte membrane with a large particle size electrolyte ensures the overall density of the electrolyte membrane.
[0033] 2. According to a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries in the present application, by doping halides in the first layer of electrolyte, the halides are evenly distributed between the negative electrode and the electrolyte to form a passivation layer, isolating the electrolyte from the side reactions of the negative electrode, inhibiting lithium dendrites, and preventing damage to the interface during lithium deposition.
[0034] 3. According to a method for preparing a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries in the present application, by doping the first layer of the electrolyte membrane with halides, only simple mixing is required without high-temperature treatment to achieve uniform distribution of halides between the negative electrode and the electrolyte, thereby forming a passivation layer to isolate the side reactions between the electrolyte and the negative electrode and inhibit the growth of lithium dendrites. The preparation method is simple and easy to operate.
[0035] 4. According to a method for preparing a composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries in the present application, the present application makes specific limitations on process conditions, coating thickness, solid content, and binder content, so that the prepared electrolyte membrane has improved mechanical strength and is easy to demold, has appropriate thickness, and has lower impedance and higher ionic conductivity.
[0036] 5. According to a method for preparing a battery of the present application, by further limiting the components and preparation method of the silver-carbon electrode, and making specific limitations on the coating thickness, drying conditions, and static pressure treatment conditions, the interfacial compatibility of the battery is improved, thereby improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0038] Figure 1 This is a graph showing the rate performance test results of a soft-pack battery involved in Example 8 of the present application;
[0039] Figure 2 This is a graph showing the effect of different isostatic pressure temperatures on the discharge performance of the soft-pack battery involved in Example 7 of the present application;
[0040] Figure 3 This is a cycle performance diagram of the soft-pack battery involved in Example 8 and Example 7 of the present application;
[0041] FIG4( a) is a graph showing the limiting current density of the composite electrolyte membrane involved in Example 9;
[0042] FIG4( b ) is a comparison chart of the discharge specific capacities of the soft-pack batteries of Example 9 and Example 7;
[0043] Figure 5 This is a cycle performance diagram of the soft pack battery involved in Example 9;
[0044] Figure 6 The figure is a cycle data diagram of the soft-pack battery involved in Comparative Example 1 and Comparative Example 2;
[0045] Figure 7 The cross-sectional SEM images of the electrolyte membranes of Comparative Example 1 and Example 8;
[0046] Figure 8 This is a graph showing the rate performance test results of the soft-pack battery involved in Comparative Example 3. DETAILED DESCRIPTION
[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0048] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0049] Example 1 Preparation of a composite electrolyte membrane 1# for inhibiting the growth of lithium dendrites in solid-state batteries
[0050] (1) mixing a sulfide electrolyte Li6PS5Cl, a solvent isobutyl isobutyrate, and a binder nitrile rubber to prepare a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 32.4%, and the content of the binder is 3%. The first electrolyte slurry is coated on the negative electrode sheet with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0051] (2) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2 to 4 μm, the solid content of the second electrolyte slurry is 39.3%, and the content of the binder is 3%. The second electrolyte slurry is coated on the first layer of the electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80°C and a vacuum drying time of 12 h to obtain a composite electrolyte membrane 1#.
[0052] Example 2 Preparation of a composite electrolyte membrane 2# for inhibiting the growth of lithium dendrites in solid-state batteries
[0053] (1) mixing a sulfide electrolyte Li6PS5Cl, a solvent isobutyl isobutyrate, and a binder nitrile rubber to prepare a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 30%, and the content of the binder is 4%. The first electrolyte slurry is coated on the negative electrode sheet with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0054] (2) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2 to 4 μm, the solid content of the second electrolyte slurry is 36.2%, and the content of the binder is 4%. The second electrolyte slurry is coated on the first layer of the electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80°C and a vacuum drying time of 12 h to obtain a composite electrolyte membrane 2#.
[0055] Example 3 Preparation of a composite electrolyte membrane 3# for inhibiting the growth of lithium dendrites in solid-state batteries
[0056] (1) sulfide electrolyte Li6PS5Cl, solvent isobutyl isobutyrate, and binder nitrile rubber are mixed to prepare a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 28.4%, and the content of the binder is 5%. The first electrolyte slurry is coated on the negative electrode sheet with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0057] (2) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2 to 4 μm, the solid content of the second electrolyte slurry is 34.8%, and the content of the binder is 5%. The second electrolyte slurry is coated on the first layer of the electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80°C and a vacuum drying time of 12 h to obtain a composite electrolyte membrane 3#.
[0058] Example 4 Preparation of a composite electrolyte membrane 5# for inhibiting the growth of lithium dendrites in solid-state batteries
[0059] The difference between Example 4 and Example 2 is that the first electrolyte slurry is further doped with halide anhydrous LiI, and the doping ratio of the anhydrous LiI is 3%.
[0060] Experimental Example 1
[0061] The composite electrolyte membranes obtained in Examples 1 to 4 were subjected to cold pressing at 300 MPa for 10 min to obtain composite electrolyte membranes that can be separated from the substrate. The electrical conductivity of the composite electrolyte membranes was tested under different environments, and the test results are shown in Table 1.
[0062] Table 1 Ionic conductivity test results
[0063]
[0064]
[0065] As shown in Table 1, it can be seen from the results of Examples 1 to 3 that, as the ratio of the binder and the solid content of the electrolyte slurry continue to change, when the coating thickness remains unchanged, the thickness of the electrolyte membrane after isostatic pressing will also change accordingly. The thickness of the electrolyte membrane with a binder ratio of 3% is 50 μm, the thickness of the electrolyte membrane with a binder ratio of 4% is 42 μm, and the thickness of the electrolyte membrane with a binder ratio of 5% is 30 μm; Example 4 is doped with anhydrous LiI, and under the same temperature conditions, its impedance is significantly reduced compared with Examples 1 to 3, and the ionic conductivity is improved.
[0066] Example 5 Preparation of a battery
[0067] (1) Preparation of silver-carbon pole piece: nano silver powder, C65 and binder PVDF glue are ball-milled and mixed to obtain a slurry, wherein the mass ratio of nano silver powder, C65 and binder is 1:3:0.1, and the concentration of binder is 10%, to obtain a silver-carbon slurry; the silver-carbon slurry is coated on a copper foil with a coating thickness of 30 μm, and dried at 30° C. for 20 min to obtain a silver-carbon pole piece;
[0068] (2) mixing sulfide electrolyte Li6PS5Cl, solvent isobutyl isobutyrate, and binder nitrile rubber to obtain a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 30%, and the content of the binder is 4%. The first electrolyte slurry is coated on the silver-carbon electrode with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0069] (3) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2-4 μm, the solid content of the second electrolyte slurry is 36.2%, and the content of the binder is 4%. The second electrolyte slurry is coated on the first electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80° C. and a vacuum drying time of 12 h to obtain an AgC / electrolyte composite electrode.
[0070] (4) The AgC / electrolyte composite electrode is laminated to the positive electrode, and the positive electrode surface loading is 12 mg / cm 2 , static pressure treatment, the pressure of static pressure treatment is 300MPah, the temperature is 25℃;
[0071] (5) Performing tab welding and vacuum packaging to obtain battery 1#.
[0072] Example 6 Preparation of a battery
[0073] (1) Preparation of silver-carbon pole piece: Nano silver powder, C65 and binder PVDF-HFP glue are ball-milled and mixed to obtain a slurry, wherein the mass ratio of nano silver powder, C65 and binder is 1:3:0.25, and the concentration of binder is 1%, to obtain a silver-carbon slurry; the silver-carbon slurry is coated on a copper foil with a coating thickness of 300 μm, and dried at 80° C. for 5 min to obtain a silver-carbon pole piece;
[0074] (2) mixing sulfide electrolyte Li6PS5Cl, solvent isobutyl isobutyrate, and binder nitrile rubber to obtain a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 30%, and the content of the binder is 4%. The first electrolyte slurry is coated on the silver-carbon electrode with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0075] (3) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2-4 μm, the solid content of the second electrolyte slurry is 36.2%, and the content of the binder is 4%. The second electrolyte slurry is coated on the first electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80° C. and a vacuum drying time of 12 h to obtain an AgC / electrolyte composite electrode.
[0076] (4) The AgC / electrolyte composite electrode is laminated to the positive electrode, and the positive electrode surface loading is 12 mg / cm 2 , static pressure treatment is carried out, the pressure of static pressure treatment is 600MPa, and the temperature is 25℃;
[0077] (5) Performing tab welding and vacuum packaging to obtain battery 2#.
[0078] Example 7 Preparation of a battery
[0079] (1) Preparation of silver-carbon pole piece: Nano silver powder, C65 and binder PVDF glue are ball-milled and mixed to obtain a slurry, wherein the mass ratio of nano silver powder, C65 and binder is 1:3:0.2, and the concentration of binder is 1%, to obtain a silver-carbon slurry; the silver-carbon slurry is coated on a copper foil with a coating thickness of 50 μm, and dried at 60° C. for 10 min to obtain a silver-carbon pole piece;
[0080] (2) mixing sulfide electrolyte Li6PS5Cl, solvent isobutyl isobutyrate, and binder nitrile rubber to obtain a first electrolyte slurry, wherein the particle size of the sulfide electrolyte is less than 1 μm, the solid content of the first electrolyte slurry is 30%, and the content of the binder is 4%. The first electrolyte slurry is coated on the silver-carbon electrode with a coating thickness of 150 mm, and allowed to stand until the surface solvent evaporates to obtain a first layer of electrolyte membrane;
[0081] (3) The sulfide electrolyte Li6PS5Cl, the solvent isobutyl isobutyrate, and the binder nitrile rubber are mixed to prepare a second electrolyte slurry; wherein the particle size of the sulfide electrolyte is 2-4 μm, the solid content of the second electrolyte slurry is 36.2%, and the content of the binder is 4%. The second electrolyte slurry is coated on the first layer of electrolyte membrane with a coating thickness of 250 μm. After the surface is dried, vacuum drying is performed at a temperature of 80°C and a vacuum drying time of 12 h to obtain an AgC / electrolyte composite electrode sheet; (4) The AgC / electrolyte composite electrode sheet is bonded to the positive electrode sheet, and the surface loading of the positive electrode sheet is 12 mg / cm 2 , static pressure treatment is carried out, the pressure of static pressure treatment is 300MPa, and the temperature is 120℃;
[0082] (5) Performing tab welding and vacuum packaging to obtain battery 3#.
[0083] Example 8
[0084] The difference between Example 8 and Example 7 is that the static pressure treatment in step (4) is 300 MPa, and the static pressure treatment is carried out at room temperature, 25°C.
[0085] Example 9
[0086] The difference between Example 9 and Example 7 is that 3% anhydrous LiI is doped when preparing the first electrolyte slurry, and the rest are the same.
[0087] Comparative Example 1
[0088] The difference between Comparative Example 1 and Example 8 is that the total coating thickness of the composite electrolyte membrane is 300 um, and the rest are the same.
[0089] Comparative Example 2
[0090] The difference between Comparative Example 2 and Example 7 is that the total coating thickness of the composite electrolyte membrane is 300 um, and the rest are the same.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 7 is that the particle size of the sulfide electrolyte in the second electrolyte slurry is less than 1 um, and the rest are the same.
[0093] Experimental Example 2
[0094] The soft-pack batteries obtained in Example 7 and Example 8 were subjected to a battery rate performance test, with a pressure of 4 MPa applied in the fixture and the test performed at 55°C. The test results are shown in Figure 1 and Figure 2 As shown. Figure 1As shown, in Example 8, three soft-pack batteries assembled from the same batch did not have short circuits in the first cycle. The battery's first cycle discharge capacity reached 178mAh / g, and the first cycle coulomb efficiency reached 80%. For the battery obtained in Example 7, after the temperature was raised, the charge and discharge capacity of the soft-pack battery at 0.05C in the first cycle had no significant difference, but at 0.1C cycle, as shown in FIG. Figure 2 As shown in the figure, the battery discharge capacity after high temperature treatment is increased from 148mAh / g to 155mAh / g, indicating that high temperature treatment has a significant effect on the discharge performance of the soft-pack battery.
[0095] The cycle performance of the soft-pack batteries obtained in Example 7 and Example 8 was compared. Figure 3 As shown by Figure 3 It can be seen from (a) that the soft-pack battery in Example 8 that has undergone 300 MPa cold treatment can cycle 20 times under 0.1C charge and discharge conditions during the subsequent cycle process, and the coulomb efficiency is maintained at 98%. However, after the battery has cycled 20 times, the coulomb efficiency of the battery decreases and a micro-short circuit occurs during charging.
[0096] like Figure 3 As shown in (b), the condition of the soft-pack battery of Example 7 after 120°C warm isostatic pressing was improved, and no short circuit occurred after 50 stable cycles, indicating that increasing the isostatic pressing temperature can further improve the interfacial compatibility of the battery, thereby improving the cycle stability.
[0097] As shown in FIG. 4( a ), FIG. 4( a ) is a graph showing the limiting current density that the composite electrolyte membrane doped with lithium iodide in Example 9 can withstand, that is, the composite electrolyte membrane doped with lithium iodide in Example 9 can withstand 1.46 mAh / cm 2 of current density.
[0098] As shown in FIG4( b ), it is a comparison chart of the discharge specific capacity of the soft-pack battery of Example 9 and Example 7. At a rate of 0.1C, the discharge specific capacity of the soft-pack battery is increased again from 155 mAh / g to 159.89 mAh / g.
[0099] like Figure 5 As shown, it is a cycle performance diagram of the soft-pack battery involved in Example 9. When the soft-pack battery of Example 9 is cycled at 0.1C, the battery is normal after 30 cycles.
[0100] The soft-pack batteries obtained in Comparative Example 1 and Comparative Example 2 were cycled and the results were as follows: Figure 6 As shown, Figure 6 (a) shows the cycle data of the soft-pack battery assembled in Comparative Example 1. The soft-packs assembled in the same batch all had obvious short circuit or overcharge in the first cycle. Figure 6(b) shows that the soft-pack battery assembled in Comparative Example 2 also has a short circuit phenomenon. Analysis shows that the composite electrolyte membrane is too thin, and cracks are very likely to occur, resulting in the growth of lithium dendrites, which may be the cause of the battery short circuit.
[0101] Comparing the electrolyte membrane thickness of Comparative Example 1 and Example 8, we can obtain Figure 7 From the cross-sectional SEM images of the electrolyte membranes of Comparative Example 1 and Example 8, it can be obtained that the thickness of the electrolyte membrane in Comparative Example 1 is 26 um, and the thickness of the electrolyte membrane in Example 8 is 42 um.
[0102] The soft pack battery obtained in comparative example 3 was subjected to rate performance test, and the results were Figure 8 .like Figure 8 As shown, the soft-pack battery obtained in Comparative Example 3 has a discharge specific capacity of 140 mAh / g under 0.1C cycle.
[0103] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery, characterized in that: It comprises a two-layer electrolyte membrane structure; the first layer of electrolyte membrane comprises electrolyte and binder; the second layer of electrolyte membrane comprises electrolyte and binder; the particle size of the electrolyte in the first layer of electrolyte membrane is less than 2um, and the particle size of the electrolyte in the second layer of electrolyte membrane is 2-10um.
2. A composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries according to claim 1, characterized in that: The first electrolyte membrane also includes a halide, and the halide is one or more of LiI, LiF, LiCl or LiBr.
3. A composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries according to claim 1, characterized in that: The electrolyte is an oxide electrolyte or a sulfide electrolyte; wherein the oxide electrolyte is LLZO or LLTO; the sulfide electrolyte is Li6PS5Cl, Li 10 SnPS 12 , Li6PS5Br and Li 10 GeP2S 12 One or more of the .
4. A composite electrolyte membrane for inhibiting the growth of lithium dendrites in solid-state batteries according to claim 3, characterized in that: The binder includes one or more of NRR, SBR, SEBS, SEPS, PTFE, PVDF, PVDF-HFP, PAA and PAA-Li.
5. A method for preparing a composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a sulfide electrolyte, a solvent, and a binder to prepare a slurry to obtain a first electrolyte slurry, coating the first electrolyte slurry on the negative electrode sheet, and allowing the slurry to stand until the surface solvent evaporates to obtain a first electrolyte membrane; (2) A sulfide electrolyte, a solvent, and a binder are mixed to prepare a slurry to obtain a second electrolyte slurry; the second electrolyte slurry is coated on the first electrolyte membrane, and the surface is dried in air and then vacuum dried to obtain a composite electrolyte membrane.
6. The method for preparing a composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery according to claim 5, characterized in that: The solvent includes one or more of isobutyl isobutyrate, butyl butyrate, dichloromethane, benzyl methane, xylene and n-decane; the mixing and slurrying in step (1) also includes adding a halide; In step (2), the vacuum drying temperature is 80°C-100°C; the vacuum drying time is 10h-14h; In step (1), the coating thickness of the first electrolyte slurry is 50-200 um; in step (2), the coating thickness of the second electrolyte slurry is 100-400 um; and the sum of the coating thickness of the first electrolyte slurry and the coating thickness of the second electrolyte slurry is greater than 300 um.
7. The method for preparing a composite electrolyte membrane for inhibiting the growth of lithium dendrites in a solid-state battery according to claim 6, characterized in that: The solid content of the first electrolyte slurry is 25%-35%, the doping ratio of the halide is 1%-10%, and the content of the binder is 3%-5%; the solid content of the second electrolyte slurry is 30%-40%, and the content of the binder is 3%-5%.
8. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a composite electrolyte membrane according to any one of claims 1 to 4 or a composite electrolyte membrane prepared by the preparation method according to any one of claims 5 to 7 located between the positive electrode and the negative electrode.
9. The method for preparing a battery according to claim 8, characterized in that: The following steps are involved: (1) Preparing a silver-carbon pole piece: mixing nano silver powder, C65 and a binder by ball milling to obtain a silver-carbon slurry; coating the silver-carbon slurry on a substrate, and drying to obtain a silver-carbon pole piece; (2) mixing a sulfide electrolyte, a solvent, a binder and a halide to prepare a slurry to obtain a first electrolyte slurry, coating the first electrolyte slurry on the silver-carbon electrode, and allowing the slurry to stand until the surface solvent evaporates, thereby forming a first electrolyte membrane on the silver-carbon electrode; (3) mixing a sulfide electrolyte, a solvent, and a binder to prepare a slurry to obtain a second electrolyte slurry; coating the second electrolyte slurry on the first electrolyte membrane, drying the surface in a vacuum, and obtaining an AgC / electrolyte composite electrode; (4) Laminating the AgC / electrolyte composite electrode sheet to the positive electrode sheet and performing static pressure treatment; (5) Performing tab welding and vacuum packaging to obtain a battery.
10. A method for preparing a battery according to claim 9, characterized in that: In step (1), the substrate includes copper foil, aluminum foil or stainless steel foil; the binder includes one or more of NRR, SBR, SEBS, SEPS, PTFE, PVDF, PVDF-HFP, PAA and PAA-Li; the mass ratio of the nano silver powder, C65 and the binder is 1:3:0.1-0.25; and the concentration of the binder is 1% to 10%.
11. The method for preparing a battery according to claim 9, characterized in that: In step (1), the silver-carbon slurry coating thickness is 30-300um, the drying temperature is 30-80°C, and the drying time is 5-20min; in step (4), the static pressure treatment pressure is 300-600MPa, and the temperature is 25-120°C.
Citation Information
Cited By
Sulfide electrolyte membrane with gradient particle size distribution and preparation method and application thereof
CN120073051A
Composite solid electrolyte layer and preparation method and application thereof
CN120413839A
